Prominence of occurrence accorded to climate change information in Tanzanian newspapers - Siyao, P.O.; Sife, A.S. (SAGE- Alexandria: The Journal of National and International Library and Information Issues, 2024)
Study was conducted to analyse degree of prominence that Tanzanian newspapers accorded to climate change information.Weargue that the level of prominence accorded to climate change information by Tanzanian newspapers is inadequate. Prioritising the coverage of climate change information in newspapers is important for facilitating its access, promotion and dissemination for awareness creation. Triangulation of quantitative content analysis and in-depth interview method approaches and a sample size of 1600 newspaper editions drawn from six Tanzanian newspapers for a span of 10 years were used. Newspaper editions were quantitatively content analysed and the frequencies at which climate change information articles were placed at the various parts of the newspapers were analysed. Findings indicate that a total of 81,162 articles were published. Of this total, only 684 (0.84%) articles covered climate change information. Furthermore, findings indicate that, of the total 684 climate change information articles, only 53 (7.6%) were placed in the front pages of the six Tanzanian newspapers for all 10 years, giving a yearly average of 5.3 articles for all newspapers and only 1 article for each newspaper per year, whereas the majority (631, 92.25%) of articles in climate change were randomly placed in the inside pages. The Chi-square test (w2¼10.000; df¼1; p value < 0.002) shows that significant differences exist between the locations of number of articles in front pages and inside pages. The findings suggest that climate change information in Tanzanian